New Insights into Endometrial Cancer 2022 - Paleari, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This open access Special Issue brings together original research and review articles on molecular oncology, with attention given to endometrial cancer. It highlights new findings, methods, and technical advances in molecular cancer research. The main feature of this Special Issue is that it is a platform for open-source sharing of significant works in the field of molecular oncology that can increase our understanding of endometrial cancer development, which may lead to the discovery of new molecular diagnostic technologies and targeted therapeutics.Topics include:Molecular methods to personalize endometrial cancer screening and detection;Identification and new aspects of cellular signaling molecules and pathways for target discovery, drug design, and personalized and gender medicine;DDI discovery in endometrial cancer management;Drug repurposing for endometrial cancer prevention/treatment;Molecular modeling studies.